The Extent at Which Undergraduate Students Use the Internet for Reading - Omotayo Olabo Obielodan; Amos Ochayi Onojah; Adenike Aderogba Onojah; Oyeronke Olufunke Ogunlade; Kefas Olumide Aliu (Universitas Pendidikan Ganesha, 2021)
This study aims to investigate the extent at which undergraduate students use the internet for reading. The study specifically, (i) Examine the extent at which undergraduate students use the internet for reading, (ii) Investigate the difference on the extent of the use of internet for reading of male and female undergraduate students, (iii) Examine the difference of extent of the internet usage on reading of undergraduate students based on areas of specialization. The study was a descriptive research of survey type. A structured questionnaire designed by the researcher was used in data collection. A simple random sampling technique was used to select 150 respondents that were involved in this study from the University of Ilorin, Ilorin, Nigeria. Frequency count, mean and percentages were used to answer the research questions. Hypothesis one was tested with independent t-test while hypothesis two was tested using Analysis of Variance (ANOVA). All hypothesis were tested at 0.05 level of significance. The findings established that Undergraduates always use the internet for reading online news, E books, Email, Health information, Jokes, Comic strips, Fashion, Food/Nutrition and Sales information. Also, there was no significant difference between the extent of the internet usage on reading of undergraduate students based on gender and areas of specialization. It was however recommended that there is a need for extensive training program organized at regular interval so that all categories of users can improve their efficiency in the use of the internet.